2014
DOI: 10.1111/trf.12521
|View full text |Cite
|
Sign up to set email alerts
|

Estimating window period blood donations for human immunodeficiency virus Type 1, hepatitis C virus, and hepatitis B virus by nucleic acid amplification testing in Southern Pakistan

Abstract: Incidence rates and estimated residual risk indicate that the current risk of transfusion-transmitted viral infections attributable to blood donation is relatively high in this country. The study recommends the parallel use of both serology and NAT screening of donated blood in countries that have high seroprevalence of these viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 25 publications
5
21
4
Order By: Relevance
“…Another study found a risk of one in 1515 donations for HIV and of one in 329 donations for HCV . In Pakistan, after NAT implementation, the residual risks are one in 62,600 of HIV and one in 13,900 of HCV …”
Section: Discussionmentioning
confidence: 99%
“…Another study found a risk of one in 1515 donations for HIV and of one in 329 donations for HCV . In Pakistan, after NAT implementation, the residual risks are one in 62,600 of HIV and one in 13,900 of HCV …”
Section: Discussionmentioning
confidence: 99%
“…2 copies/mL) has a nearly 100% probability to be infectious when 20 mL of plasma in an RBC component is transfused; one therefore can assume that 100% of WP donations would have been infectious with a MID 50 of 3.2 virions. In our study, only two of 23 (9%) WP samples had VL below the qPCR quantification limit, whereas in a recent study from Southern Pakistan, 16/27 (59%) TaqMan qPCR–reactive WP donations reportedly had VLs below the quantification limit; we suspect that a large proportion of the latter cases represented false‐positive NAT results that resulted in an HCV‐NAT–yield rate (1:1530) that was higher than in our study (1:7485). In countries where donor follow‐up for confirmation of NAT‐yield donations is not feasible we recommend the use of the FFP unit for careful preparation of archive samples for confirmation testing to avoid false‐reactive NAT results due to contamination.…”
Section: Discussionmentioning
confidence: 99%
“…This clearly demonstrates the high value of the combined serological and nucleic acid screening of blood donors. Based on these, other countries have established, along with serological screening, parallel nucleic acid testing of donated blood, conferring more safety for blood supply [19,20]. Despite the high cost of this screening combination, it remains cost-effective given the extra safety that it confers to blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inadequate sensitivity of these assays to detect these viruses during the window periods of the infections poses a major threat of infected blood units getting into the blood supply undetected. A number of countries have established, along with serological screening, parallel nucleic acid testing of donated blood [19,20].…”
Section: Introductionmentioning
confidence: 99%